If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(8v-3)+9v=5(v+3)
We move all terms to the left:
-2(8v-3)+9v-(5(v+3))=0
We add all the numbers together, and all the variables
9v-2(8v-3)-(5(v+3))=0
We multiply parentheses
9v-16v-(5(v+3))+6=0
We calculate terms in parentheses: -(5(v+3)), so:We add all the numbers together, and all the variables
5(v+3)
We multiply parentheses
5v+15
Back to the equation:
-(5v+15)
-7v-(5v+15)+6=0
We get rid of parentheses
-7v-5v-15+6=0
We add all the numbers together, and all the variables
-12v-9=0
We move all terms containing v to the left, all other terms to the right
-12v=9
v=9/-12
v=-3/4
| 29=m-210 | | -3(u+2)=7u-8+4(2u+1) | | 60+60=x0+1 | | 8=m/8+9 | | 1000=2m | | 29=2z+z+z+2+6+5 | | 4z/9=3 | | p+847=111 | | 22.57=-1.4+5.1v | | 45-0.25x=0.5 | | 8=g/27 | | 14=z+z-1+2+3 | | 557=z+773 | | 2(v-2)=2v+3-2(-3v-4) | | 3-3k=-45 | | x-6+57=90 | | ×=4.2×+3y=44 | | s+243=985 | | 7v-8=4(v+4) | | X+8/3x=8/3x | | p-51=15 | | 22=2(y-7)-6y | | u+12=82 | | w+34=80 | | -7(-3u+3)-4u=3(u-8)-5 | | (12y-6)/6=2y-1 | | 6(u-6)=8u-38 | | d−–130=791 | | q-149=2 | | 3(w+5)-5w=19 | | d-67=4 | | 2(4x+7)=6/ |